ANALYSIS OF PACKAGING FUNCTION ON CONSUMER’S PERCEPTION OF PRODUCT QUALITY ON VICTORIA’S SECRET BODY MIST - Tumengkol, Vicaristy Amanda; Pangemanan, Sifrid S.; Mekel, Peggy A. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Increasingly tight competitive world where companies are competing to, attract         the attention of buyers of product is needed to make the product they produced were sold out. Not easily granted, but they should to create new ideas of each of their companies. So the form of product packaging determines the marketing strategy of a variety of companies. The purpose of this research is to analyze the influence of Packaging function (Protective, promoting, storage and environmental friendly) on consumer’s pereption of product quality both partially and simultaneously. The population observed is people who have purchased Victoria’s Secret body mist with sample size as many as 100 respondents. The data are analyzed using several statistical techniques. The method used in this research is multiple regressions. The Conclusion is Packaging Function which are Protective, Promote, Storage, and Environmental Friendly are influencing on Consumer’s Perception of product Victoria’s Secret Body Mist both simultaneously and partially. This study suggests to the management of company that produce Victoria’s Secret Body Mist to see about Protecting, Promote, Storage, and Environmental Friendly that will ultimately influence on Consumer’s Perception of Product Quality. Keywords: packaging, consumer’s perception